2013
DOI: 10.1016/j.cemconcomp.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of semi-solid fresh cement pastes and mortars in orifice extrusion

Abstract: Short fiber-reinforced semi-solid fresh cement pastes and mortars, tailored for extrusion, have much lower water-to-binder ratio and higher viscosity than normal cement pastes or mortars. The rheology of these pastes or mortars cannot be characterised by traditional rheology test methods suitable for normal fresh cement pastes or mortars with much greater water-to-binder ratio and lower viscosity. In this paper, orifice extrusion is employed to calibrate rheology of the semi-solid fresh cement mortar. An analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…Because of the limited extrusion distance (about 13.5 mm) by each driving velocity in our test, the slight reduction of frictional resistance was hard to be clarified. The decreasing trend was also not clear in the results of Zhou et al [26]. Thus, we assumed the inner wall friction was consistently the same in the measuring zone.…”
Section: Extrusion Testmentioning
confidence: 69%
See 1 more Smart Citation
“…Because of the limited extrusion distance (about 13.5 mm) by each driving velocity in our test, the slight reduction of frictional resistance was hard to be clarified. The decreasing trend was also not clear in the results of Zhou et al [26]. Thus, we assumed the inner wall friction was consistently the same in the measuring zone.…”
Section: Extrusion Testmentioning
confidence: 69%
“…As reported by Panda et al [8], the amount of ordinary Portland cement (OPC) forms more than 70% of the binder in most of the available cementitious materials for 3DCP. To satisfy the required fresh properties of 3D printable concrete, such as pumpability and extrudability, the content of aggregate is significantly reduced, and environmental-friendly fabrication method has been used in the cementitious materials industry for a long time [26] before applied in 3DCP. According to Perrot et al [27], it is feasible to use a ram extruder as a rheo-tribometer to calculate the extrusion factors of the high yield fluids, such as bulk and shear yield stresses, wall friction yield stress, and others.…”
Section: Introductionmentioning
confidence: 99%
“…Alfani and Guerrini (2005) reviewed the most promising 'nontraditional' rheology test methods for concentrated and cohesive extrudable fresh cement-based materials and found that those 'promising' test methods were initially developed for materials such as plastics, rubber, clays, soils and metals, rather than traditional cement pastes or mortars with high flowability. Zhou et al (2013) Although the Hatschek method is a continuous process, composites made by this method are usually brittle (Li and Mu, 1998). The process generates a high level of wastewater and delamination of layers has been found in cement-based products made by this method during freeze-thaw cycles (Shao and Qiu, 2002).…”
Section: Key Factors To the Extrusion Of Cementbased Materialsmentioning
confidence: 99%
“…However, it is not possible to use one single test to characterise the coupled elasto-visco-plastic rheological properties of cement-based materials tailored for extrusion (Zhou et al, 2013). Alfani and Guerrini (2005) reviewed the most promising 'nontraditional' rheology test methods for concentrated and cohesive extrudable fresh cement-based materials and found that those 'promising' test methods were initially developed for materials such as plastics, rubber, clays, soils and metals, rather than traditional cement pastes or mortars with high flowability.…”
Section: Key Factors To the Extrusion Of Cementbased Materialsmentioning
confidence: 99%
See 1 more Smart Citation